Examining the Effects of Sports on Borderline Personality, Violence and Crime Tendency - Savaş Aydın (Van Yüzüncü Yıl Üniversitesi Eğitim Fakültesi Dergisi)
The aim of this study is to examine the relationship between borderline personality traits and tendencies toward violence and crime among university students in the context of sports participation and demographic variables. Borderline personality traits were specifically addressed, as they are directly linked to behaviors such as impulsivity, poor anger control, and aggression, which are closely associated with violence and criminal tendencies. A total of 384 students, 151 male and 233 female, studying at university and selected by random sampling method participated in this study, which was conducted with a quantitative approach based on the descriptive survey model. Borderline Personality Questionnaire (BPQ), Borderline Evaluation of Severity over Time (BEST), Measures of Criminal Attitudes and Associates and a demographic information form developed by the researcher were used as data collection tools. Data were analyzed using SPSS program. Since normality was not provided in the data, Mann-Whitney U test was used in paired group comparisons, Kruskal-Wallis H Test was used in multiple group comparisons and Spearman Correlation Test was used to examine the relationship between variables. Based on the findings obtained in the study, significant differences were found between the scores of the Borderline Personality Questionnaire, Borderline Evaluation of Severity over Time, Measures of Criminal Attitudes and Associates of the university students and the variables of gender, sports status, sports year, class level and faculty (p